2022
DOI: 10.4149/neo_2022_211006n1410
|View full text |Cite
|
Sign up to set email alerts
|

ARHGAP17 enhances 5-Fluorouracil-induced apoptosis in colon cancer cells by suppressing Rac1

Abstract: Colon cancer is a common cause of death in the world, and its main cause of therapy failure is chemoresistance. Apoptosis is de-regulated in colon cancer and is one key mechanism of cancer treatment. We recently reported that reduced expression of ARHGAP17, a Rho GTPase activating protein, correlated with a poor prognosis of colon cancer patients. Here we investigated the role of ARHGAP17 in apoptosis induced by 5-Fluorouracil (5-FU) in human colon cancer cells and in mouse xenograft tumor model. We observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Our report is the first to describe ARHGAP17 at invadopodia and a direct mechanism regarding the link between ARHGAP17 and cancer cell invasion. ARHGAP17 has been previously characterized as a tumor suppressor and found to be downregulated in a variety of cancers, including colon, breast, and cervical, where it functions to inhibit migration and invasion ( Guo et al, 2019 ; Kiso et al, 2018 ; Pan et al, 2018 ; Pan et al, 2022 ; Tian et al, 2022 ). ARHGAP17 is downregulated by VEGF/NRP1 signaling in TNBC which was associated with increased Cdc42 activity, filopodia formation, and cell migration ( Kiso et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our report is the first to describe ARHGAP17 at invadopodia and a direct mechanism regarding the link between ARHGAP17 and cancer cell invasion. ARHGAP17 has been previously characterized as a tumor suppressor and found to be downregulated in a variety of cancers, including colon, breast, and cervical, where it functions to inhibit migration and invasion ( Guo et al, 2019 ; Kiso et al, 2018 ; Pan et al, 2018 ; Pan et al, 2022 ; Tian et al, 2022 ). ARHGAP17 is downregulated by VEGF/NRP1 signaling in TNBC which was associated with increased Cdc42 activity, filopodia formation, and cell migration ( Kiso et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The GAP activity of RICH1 and regulation of Cdc42 by RICH1 is required for maintaining proper tight junctions in epithelial cells ( 21 ). RICH1 is widely distributed and highly expressed in human heart and placenta tissues ( 23 ), and it has been reported that RICH1 has multiple functions in vivo ( 24 26 ). RICH1 can inhibit the activity of Rac1 by catalyzing the cleavage of Rac1-GTP to Rac1-GDP, which then inhibits the MAPK signaling pathway, which in turn reduces cellular proliferation and tumorigenesis ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%